ENZYMES: Catalysis, Kinetics and Mechanisms - Punekar, N. S. (Springer, 2018)
Enzymes are the lead actors in the drama of life. Without these molecular machines the genetic information stored in DNA is worthless. With rising attention to the fashionable fields like molecular biology, genetic engineering, and biotechnology, the techniques to manipulate DNA have occupied center stage. Being popular, many concepts of molecular biology/genetic engineering are now introduced to undergraduates. Unfortunately, this has happened at the cost of other fundamental facets of biology, including enzymology. In the excitement to collate volumes of data for Systems Biology (and the various “Omics” fashions), the beauty and vigor of careful analysis – one enzyme at a time – is neglected. It is an intellectual challenge to assay individual enzymes while avoiding complications due to others – an almost forgotten activity in modern biology. Many in the present generation assume that performing one standard assay will tell you everything about that enzyme. While biochemists spent lifetimes on a single native enzyme, the notion today is that one can characterize a mutant in the morning! Over the last three decades devoted enzymologists have become a rare breed. Many Biology teaching programs have expanded in the areas of molecular and cellular biology while they manage with a makeshift enzymology instructor. New students who are attracted to the study of enzymes do exist, but they find themselves in a very bleak teaching environment. Not surprisingly their numbers are dwindling. Reservoirs that are not replenished may soon run dry.